Ionization and hydrolysis of dinitrogen pentoxide in low-temperature solids: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Agreiter, J.; Frankowski*, M.; Bondybey, V. E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Solid layers of interest for the chemistry of polar stratospheric clouds were investigated. Mixtures of covalent N2O5 and water in various molar ratios are deposited from vapor phase on a cold 12 K substrate. By repeatedly recording Fourier transform infrared spectra of the samples during gradual warm up to200 K over a period of several hours the hydrolysis process can be followed. At each concentration the process is found to proceed in several distinct steps with sharp temperature thresholds. In samplescontaining only small amounts of water the covalent N2O5 is first around 110 K converted to an ionic nitronium nitrate, and only in a subsequent step NO2+NO3- reacts to nitric acid.